MUTUAL IMPACT OF HEDGE ACCOUNTING AND THE ACCOUNTING PRACTICES ON MEDIUM ENTERPRISES PERFORMANCE - Assistant Professor, Emad Al-Harash (Scholars Digest Publishing, 2024)
This research assesses the impact of the application of requirement of application of hedge accounting and accounting practices together on Iraq medium enterprises performance by studying the impact of requirements application of hedge accounting on Iraq medium enterprises performance firstly, then study the impact of accounting practices on medium enterprises performance secondly, then study the impact of hedge accounting on accounting practices in medium enterprises thirdly, then study the impact of accounting practices on requirements application of hedge accounting in medium enterprises fourthly and then study the impact of mutual influence for the application of requirement of application of hedge accounting and the accounting practices together on Iraq medium enterprises performance finally, by study the mutual influence for the application of hedge accounting and the accounting practices on Iraq medium enterprises performance. Overall, the study supported the hypothesis that there is a mutual influence between the application of hedge accounting and accounting practices on medium enterprises' performance in Iraq. The results of the research show that the requirements of hedge accounting and the accounting practices together can affect the choice of the medium enterprises in Iraq to adopt the best method of hedge accounting and the accounting practices adoption, and the statistical analysis results show that there is a very good level of agreement for the employees who are currently working in medium enterprises about the effect of mutual influence for the application of hedge accounting and the accounting practices on Iraq medium enterprises performance.
Keywords: hedge accounting, accounting practices, medium enterprises, and performance.